PALE GLOBE ALONE IN GLOOM”: THE CURSE OF BIRTH IN BECKETT’S - Saeed, Asst. Prof. Dr. Zanyar Faiq (Sulaimani Journal for Humanities, 2023)
To Samuel Beckett, being born into the earthly life is a sin for which the humankind should suffer their entire life. Hence, this paper claims that, in A Piece of Monologue, birth is considered the beginning of a tortuously prolonged process of dying. In the play, Beckett implies that since human beings’ end is already in their beginning, their life, which is a process of dragging death behind, is meaningless, purposeless, valueless, tedious, almost impossible to apprehend and, therefore, unworthy of living. However, since Beckett denies his characters the choice of committing suicide, they are damned to existence. This elongated process of dying moves within a vicious circle that has neither a closure nor an exit. Although death may apparently provide a closure to a person’s existential pain, the process of dying continues for humankind whose existence continues because of birth. The approach adopted in supporting this claim is based on examples from the play, historical facts, scholarly opinions, and intellectual concepts pertaining to absurdism. The discussion and conclusion of this paper will better acquaint the readers with the philosophy of absurdism and Beckett’s personal world view. This, in turn, could help them avoid those ideas that may make them think that life is absurd to an extent that might prevent them from serving themselves and humanity with their positive thoughts in one way or another. Such acquaintance could hopefully provide the readers with mechanisms for inhibiting such negative thinking.
Keywords: Keywords A Piece of Monologue; Absurdism; Atheism; Curse of Birth; Existentialism; Naturalism; Nihilism; Pale Globe; Samuel Beckett